Global Screening of LUBAC and OTULIN Interacting Proteins by Human Proteome Microarray - Zhou, Lijie; Ge, Yingwei; Fu, Yesheng; Wu, Bo; Zhang, Yong; Li, Lei; Cui, Chun-Ping; Wang, Siying; Zhang, Lingqiang (Frontiers in Cell and Developmental Biology, 2021)
Linear ubiquitination is a reversible posttranslational modification, which plays key roles in multiple biological processes. Linear ubiquitin chain assembly complex (LUBAC) catalyzes linear ubiquitination, while the deubiquitinase OTULIN (OTU deubiquitinase with linear linkage specificity, FAM105B) exclusively cleaves the linear ubiquitin chains. However, our understanding of linear ubiquitination is restricted to a few substrates and pathways. Here, we used a human proteome microarray to detect the interacting proteins of LUBAC and OTULIN by systematically screening up to 20,000 proteins. We identified many potential interacting proteins of LUBAC and OTULIN, which may function as regulators or substrates of linear ubiquitination. Interestingly, our results also hint that linear ubiquitination may have broad functions in diverse pathways. In addition, we recognized lymphocyte activation gene-3 (LAG3, CD223), a transmembrane receptor that negatively regulates lymphocyte functions, as a novel substrate of linear ubiquitination in the adaptive immunity pathway. In conclusion, our results provide searchable, accessible data for the interacting proteins of LUBAC and OTULIN, which broaden our understanding of linear ubiquitination.